Automation of Library Circulation - Gowri, R.; Yadumani (Journal of Information and Knowledge, 1986)
The software developed to automate the Indian Institute of Science library's circlation system has been discussed in this paper. The objectives of the automated system are formulated after giving a thorough study of the major distinguishing features and the objectives of the existing system. There are eight procedures incorporated in the system to achieve the objectives. The invoking of these procedures are done by keying commands of length 18 characters. Once a procedure is invoked It expects a set of inputs, and these are accepted through the machine's conversation with the user. The questions asked by the system during the conversation are self-explanatory and it makes it easy and simple to use the system. The system has been developed to work on a single terminal extending equal facilities to the staff and the user. In this paper suggestions are made to adopt the system to work on two terminals to improve the service to the user. While discussing the cost efficiency of the system greater emphasis is given to the factors which contribute to the cost of the system than to the actual figures.